An introduction to the chemistry of the sea - Pilson, Michael E. Q. (Cambridge : Cambridge University Press, 2013)
'Fully updated and expanded, this new edition provides students with an accessible introduction to marine chemistry. It highlights geochemical interactions between the ocean, solid earth, atmosphere and climate, enabling students to appreciate the interconnectedness of Earth's processes and systems and elucidates the huge variations in the oceans' chemical environment, from surface waters to deep water. Written in a clear, engaging way, the book provides students in oceanography, marine chemistry and biogeochemistry with the fundamental tools they need for a strong understanding of ocean chemistry. Appendices present information on seawater properties, key equations and constants for calculating oceanographic processes. New to this edition are end-of-chapter problems for students to put theory into practice, summaries to allow easy review of material and a comprehensive glossary. Supporting online resources include solutions to problems and figures from the book'--
Machine generated contents note: Preface; 1. Introduction; 2. The water in seawater; 3. Salinity, chlorinity, conductivity, and density; 4. Major constituents of seawater; 5. Simple gases; 6. Salts in solution; 7. Carbon dioxide; 8. Nutrients; 9. Trace metals and other minor elements; 10. Radioactive clocks; 11. Organic matter in the sea; 12. Anoxic marine environments; 13. Exchanges at the boundaries; 14. Chemical extraction of useful substances from the sea; 15. Geochemical history of the oceans; Appendix A. The chemical elements; Appendix B. Symbols, units, and nomenclature; Appendix C. Physical properties of seawater; Appendix D. Gases; Appendix E. Carbon dioxide; Appendix F. Dissociation constants and pH scales; Appendix G. Solubility of calcium carbonate; Appendix H. Effects of pressure; Appendix I. Radioactive decay; Appendix J. Geochemical reservoirs, and some rates; Appendix K. Sound absorption; Glossary; References; Index.
Includes bibliographical references and index.
Keywords: Chemical oceanography; SCIENCE / Earth Sciences / Oceanography